2016
DOI: 10.2147/dmso.s109007
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of metabolic syndrome: a cross-sectional survey of general medical outpatient clinics using National Cholesterol Expanded Program-Adult Treatment Panel III criteria in Botswana

Abstract: BackgroundLow- and middle-income countries, including Botswana, are facing rising prevalence of obesity and obesity-related cardiometabolic complications. Very little information is known about clustering of cardiovascular risk factors in the outpatient setting during routine visits. We aimed to assess the prevalence and identify the determinants of metabolic syndrome among the general outpatients’ attendances in Botswana.MethodsA cross-sectional study was conducted from August to October 2014 involving outpat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 26 publications
2
16
2
Order By: Relevance
“…Of the two remaining studies, Gebremichael et al 41 (n = 1 of high quality, 86%) reported that the was no statistically significant association between hypertension and food insecurity exposure in adultsonly study participants. In contrast, Omech et al 45 (n = 1 of average quality, 71%) in adults-only study participants, found that although consumption of vegetables, fruit, and berries showed a protective effect on dyslipidaemia and obesity, it was not statistically significant; thus the association between dyslipidemia, obesity, and exposure to food insecurity was inconclusive.…”
Section: Results Of Individual Studies A) Evidence On the Associationmentioning
confidence: 90%
See 2 more Smart Citations
“…Of the two remaining studies, Gebremichael et al 41 (n = 1 of high quality, 86%) reported that the was no statistically significant association between hypertension and food insecurity exposure in adultsonly study participants. In contrast, Omech et al 45 (n = 1 of average quality, 71%) in adults-only study participants, found that although consumption of vegetables, fruit, and berries showed a protective effect on dyslipidaemia and obesity, it was not statistically significant; thus the association between dyslipidemia, obesity, and exposure to food insecurity was inconclusive.…”
Section: Results Of Individual Studies A) Evidence On the Associationmentioning
confidence: 90%
“…39 The remaining six studies recruited participants from both rural and urban settings. [40][41][42][43][44][45] Overall, the studies selected for inclusion (n = 22 studies) involved a total of 26 609 participants, 12 453 (46.8%) participants were males, and one study recruited only women of reproductive age living in informal settlements in Accra, Ghana 29 . The distribution of the rest of the studies by countries was as follows: 4 from Ethiopia, 25,27,40,41 ; 1 Nigeria, 24 ; 1 Madagascar, 26 ; 3 Ghana, 29,38,39 ; 1 Zambia, 37 ; 2 Tanzania, 28,35 ; 1 Malawi, 34 ; 1 Cameroon, 33 ; 2 Sudan, 30,31 ; 1 Burkina Faso, 42 ; 1 Kenya, 32 ; 1 Botswana, 45 and 3 studies from South Africa 36,43,44 .…”
Section: A) Study Participants and Geographical Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic syndrome is one of the major pandemics that affect health across the globe 2 . The prevalence of metabolic syndrome is approximately 30% in the world 3 5 , and ranges from 7% to 32% in China 6 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Author(s) agree that this article remain permanently open access under the terms of the Creative Commons Attribution License 4.0 International License systems, especially in industrialized countries and is associated with several other comorbidities, such as metabolic syndrome, hypertension, type-2 diabetes, dyslipidemia and cardiovascular risk, with significant morbidity and mortality (Bocco et al, 2016;Omech et al, 2016). Worldwide, at least 2.8 million people die each year as a result of being overweight or obese (Organization, 2016).…”
Section: Introductionmentioning
confidence: 99%